2021
DOI: 10.1097/tp.0000000000003607
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Fatal Graft-versus-host Disease After Liver Transplantation

Abstract: Background. Graft-versus-host disease (GVHD) after liver transplantation (LT) is a rare but serious complication. The aim of this study is to identify risk factors, including immunosuppressive regimens, for mortality due to GVHD (fatal GVHD). Methods. Using data from the Organ Procurement and Transplantation Network and United Network for Organ Sharing registry, 77 416 adult patients who underwent LT between 2003 and 2018 were assessed. Risk factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
1
19
1
1
Order By: Relevance
“…Kitajima et al recently evaluated 121 patients with fatal GVHD reported in the United Network for Organ Sharing database and found that induction therapy with basiliximab was an independent risk factor for fatal GVHD. ( 16 ) Our analysis did not confirm this association and found that induction therapy with ATG and not basiliximab was significantly associated with the development of GVHD. The potential reasons for the discrepancy include our smaller number of patients with GVHD and our inclusion of all patients with GVHD, as opposed to only patients who had fatal GVHD.…”
Section: Discussioncontrasting
confidence: 71%
“…Kitajima et al recently evaluated 121 patients with fatal GVHD reported in the United Network for Organ Sharing database and found that induction therapy with basiliximab was an independent risk factor for fatal GVHD. ( 16 ) Our analysis did not confirm this association and found that induction therapy with ATG and not basiliximab was significantly associated with the development of GVHD. The potential reasons for the discrepancy include our smaller number of patients with GVHD and our inclusion of all patients with GVHD, as opposed to only patients who had fatal GVHD.…”
Section: Discussioncontrasting
confidence: 71%
“…A recent analysis utilizing a nationwide database found several factors in the LT population associated with developing fatal GVHD, including a donor age more than 20 years younger than the recipient and basiliximab induction. 14 However, this study was unable to differentiate nonfatal GVHD from patients without GVHD, and it is unclear if these factors are predictive for mortality in those that develop GVHD or simply development of the disease.…”
Section: Discussionmentioning
confidence: 86%
“…7 Other identified risks factors include recipients with alcoholic liver disease, autoimmune hepatitis, glucose intolerance, 8 young donors and recipient-donor age difference of >20 years. 9 Prognosis is poor with a reported 6-month mortality rate of 73%. 10 Death often results from sepsis, bleeding, and multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%